Influência do teor de amilose e beneficiamento do arroz na resposta biológica em ratos - Denardin, Cristiane Casagrande (2008)
Rice is one of the most important cereal consumed worldwide, being the main source of energy for 1.2 billion of people. Besides, rate and extension of rice starch digestion can be influenced by different factors, including amylose content and grain processing (parboiling). However, Brazilian rice consumption fell 13.5% in the last few years being pasta a substitute for this cereal. The objective of this work was to evaluate the effects of rice grains with different amylose content (high, intermediated and low) or submitted to parboiling in the rat biological response, as well as to determinate the effect of to replace the rice by pasta. Male Wistar rats were fed with diets containing a) white grains of rice cultivars with high (IRGA 417), intermediate (IRGA 416) and low (Mochi) amylose content; b) white and parboiled grains of rice cultivar IRGA 417; and c) white grains of rice cultivar IRGA 417 and pasta (spaghetti); after cooked, hot-air dried at 50°C and grounded. Amylose:amylopectin ratio significantly affected rice starch digestion in the gastrointestinal tract, being rats fed with high amylose content (IRGA 417) treatment showed lower feed intake, body weight gain, apparent digestibility, postprandial blood glucose response, serum total cholesterol and triglycerides levels and pancreas weight, reduced fecal pH, and higher fecal water content, nitrogen excretion, fasting serum glucose concentration and liver weight. The structural change of rice components caused by parboiling provoked variations in different body metabolic parameters, being rats fed with parboiled rice treatment showed higher body weight gain, feed intake, nitrogen excretion, serum triglycerides and uric acid levels, and pancreas weight, and lower feed conversion, fecal pH, albumin and serum HDL cholesterol than white rice treatment. Pasta replacing rice consumption resulted in rats with lower wet and dry fecal production, nitrogen excretion and serum HDL cholesterol, and higher apparent dry matter digestibility, serum uric acid and total cholesterol levels, and kidney and pancreas weights.